Assembly of biomimetic microreactors using caged-coacervate droplets. Issue 6 (5th January 2023) - Jobdeedamrong, Arjaree; Cao, Shoupeng; Harley, Iain; Crespy, Daniel; Landfester, Katharina; Caire da Silva, Lucas
Abstract : Caged microreactors were constructed by Pickering stabilization of complex coacervate droplets with silica nanoparticles. The size of the nanoparticles determined the molecular transport into the microreactors. Abstract : Complex coacervates are liquid-like droplets that can be used to create adaptive cell-like compartments. These compartments offer a versatile platform for the construction of bioreactors inspired by living cells. However, the lack of a membrane significantly reduces the colloidal stability of coacervates in terms of fusion and surface wetting, which limits their suitability as compartments. Here, we describe the formation of caged-coacervates surrounded by a semipermeable shell of silica nanocapsules. We demonstrate that the silica nanocapsules create a protective shell that also regulates the molecular transport of water-soluble compounds as a function of nanocapasule size. The adjustable semipermeability and intrinsic affinity of enzymes for the interior of the caged-coacervates allowed us to assemble biomimetic microreactors with enhanced colloidal stability.